Effect Of Drying Tempeature And Various Blanching Methods On The Quality Of Cassava Leaf Flour (Manihot esculenta C): Pengaruh Temperatur Pengeringan Dan Berbagai Metode Blansing Terhadap Mutu Tepung Daun Singkong (Manihot esculenta C) - Rahma, Selma Amelia; Saidi, Ida Agustini (Universitas Muhammadiyah Sidoarjo, 2023)
This research was conducted because of the high protein content in cassava leaves which causes cassava leaves to be easily damaged, therefore turning cassava leaves into flour will extend the shelf life of cassava leaves. The method used in this study was a randomized block design (RBD) using 2 factors with 9 treatments repeated 3 times, so that 27 experimental units were obtained. This research uses ANOVA analysis which is then further tested with a 5% level of Honest Significant Difference (BNJ). The results showed that cassava leaf flour had a significant interaction on water content and protein content, while the antioxidant activity had no significant effect. The results showed that the lowest value for the parameter of water content was 6.05%, the highest value for the parameter for protein content was 27.10%, the highest value for the antioxidant parameter was 79.59%.